2017
DOI: 10.2147/ott.s123518
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-148a suppresses proliferation and invasion potential of non-small cell lung carcinomas via regulation of STAT3

Abstract: Lung cancer has the highest morbidity and mortality in the world, and non-small cell lung carcinomas (NSCLC) account for 80% of cases of lung cancer. The mechanism of NSCLC is still largely unknown, and finding novel targets is of great importance for the treatment of NSCLC. The current study was designed to evaluate the role of miR-148a in NSCLC cell proliferation and invasion and to investigate the possible molecular mechanisms. We found that miR-148a expression was decreased in NSCLC tissues and cell lines.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 38 publications
1
18
0
Order By: Relevance
“…Activation of STAT3 can contribute to oncogenesis by inducing tumor angiogenesis (Siveen et al, ; Swiatek‐Machado et al, ). miR‐148a can restrain NSCLC development via regulating STAT3 (He & Xue, ). Here, we found that STAT3 was a target of miR‐17 and miR‐17 can negatively regulate STAT3 expression.…”
Section: Discussionmentioning
confidence: 99%
“…Activation of STAT3 can contribute to oncogenesis by inducing tumor angiogenesis (Siveen et al, ; Swiatek‐Machado et al, ). miR‐148a can restrain NSCLC development via regulating STAT3 (He & Xue, ). Here, we found that STAT3 was a target of miR‐17 and miR‐17 can negatively regulate STAT3 expression.…”
Section: Discussionmentioning
confidence: 99%
“…By targeting STAT3, miR‐1181 can inhibit pancreatic cancer development and can serve as a therapeutic target (Wang, Lu et al, ). miR‐148a can restrain non‐small cell lung carcinomas via regulating STAT3 (He & Xue, ). STAT3 was demonstrated to be a direct target of miR‐125b by bioinformatics research.…”
Section: Discussionmentioning
confidence: 99%
“…Li et al (27) demonstrated that miR-148a suppressed epithelial-mesenchymal transition by targeting ROCK1 in NSCLC cells. He and Xue (15) reported that miR-148a inhibited NSCLC cell proliferation and invasion via inhibition of STAT3 expression. In the current study, E2F3 was confirmed to be a direct target gene of miR-148a in lung adenocarcinoma cells.…”
Section: Discussionmentioning
confidence: 99%
“…healthy controls. Additionally, miR-148a has been reported to serve a suppressive role in NSCLC (13)(14)(15). However, the regulatory mechanism of miR-148a in lung adenocarcinoma growth remains largely unclear.…”
Section: Microrna-148a Inhibits Cell Proliferation and Cell Cycle Promentioning
confidence: 99%